A DEA model with identical weight assignment based on multiple perspectives. (1st January 2012) - Yang, Xiaopeng; Morita, Hiroshi
For a complicated banking system with various financial attributes, there are usually different classifications of inputs and outputs from the perspectives of different stakeholders. In order to obtain the highest efficiency score, different perspectives tend to select different weight assignment schemes, even in evaluating the same bank. In order to balance multiple perspectives (Pareto optimality) based on their market statuses and evaluate DMU more objectively, we propose a new DEA model incorporating Nash bargaining game (NBG) theory, which focuses on seeking an identical weight assignment scheme to cater to multiple perspectives.